Políticas de avaliação em larga escala e a construção de um currículo nacional para a educação básica - Marilda Pasqual Schneider (EccoS – Revista Científica)
Large-scale assessments comprise the framework of educational policies imposed by the Brazilian Government in recent decades with the aim of strengthening the regulatory action and the symbolic and operational power of the state. These policies bring together the realization of standardized examinations to the issues of curriculum and educational quality. Based on authors from the sociology, the purpose of this text is to understand and analyze how and why changes are observed in schools after the deployment of a large-scale assessment system for basic education. Embodied in the analysis of information gathered from the teachers of public schools, it highlights the trend that the standardized exams indicate which knowledge is relevant, delimiting, by extension, what should or should not be taught. It concludes by calling attention to the need to analyze the effects of large-scale assessments in the curriculum, in the work of teachers and in the students’ learning on basic education.